Pengaruh Kualitas Pelayanan, Harga, dan Promosi terhadap Kepuasan Pelanggan di Boy Supermarket Batam - Azalia Putri Saqina; Yandra Rivaldo; Netti Syafitri (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2026)
This study aims to analyze the effect of service quality, price, and promotion on customer satisfaction at Boy Supermarket Batam. The background of this research is based on the importance of customer satisfaction in enhancing customer loyalty and maintaining competitiveness in the increasingly competitive retail industry. The independent variables in this study are service quality, price, and promotion, while the dependent variable is customer satisfaction. This research employs a quantitative method with descriptive and associative approaches. Data were collected through questionnaires distributed to customers of Boy Supermarket Batam. The data analysis techniques used include validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, and F-test. The results show that partially, service quality, price, and promotion have an effect on customer satisfaction. Simultaneously, these three variables also have a significant effect on customer satisfaction. The descriptive analysis indicates that all variables are in a good category; however, several aspects still need improvement, such as service consistency, price competitiveness, and promotion intensity. The conclusion of this study is that service quality, price, and promotion are important factors in shaping customer satisfaction. Therefore, management is recommended to improve service quality consistently, maintain price transparency and competitiveness, and enhance promotional effectiveness in order to increase customer satisfaction.